Evaluating the Implementation of Project-Based Learning (PjBL): A Study at the English Language Education Study Program, Faculty of Education, Jambi University - Adrefiza, Adrefiza; Ridha, Ahmad; Habizar, Habizar (Innovare Journal of Education, 2024)
The present study evaluated the implementation of Project-Based Learning (PjBL) by the lecturers at the English Language Education Study Program, Faculty of Education, Jambi University. Using information from 100 selected students through electronic email questionnaires with Likert’s 5 points-scale of frequency levels (never to always) concerning ten PjBL main principles, the results fell into the “good” category with an average score of (3.17). Principle 1 (Starting the class with driving questions/issues/problems); 2 (Students work independently in small groups based on a selected project); and 7 (The groups do project presentations for feedback) received the highest rate in the evaluation with an average score of (3.8) each, followed by the principle 4 (The groups discuss, pose, inquire, analyze, and evaluate issues or problems related to the topics) and the principle 9 (The students develop new soft-skills e.g. collaboration, problem-solving, critical thinking, and management skills) with the average scores of (3.5 & 3.2) respectively. The other principles such as “collecting information, facts, evidence, and data outside the classroom for the project work” (principle 5) and “receiving feedback and controls from the lecturers” (principle 6), still need to be improved and developed to achieve better results in the future.